Dietary n-3 fatty acid effects on neutrophil lipid composition and mediator production. Influence of duration and dosage. - Chilton, F H; Patel, M; Fonteh, A N; Hubbard, W C; Triggiani, M (The Journal of Clinical Investigation, 1993)
Healthy volunteers supplemented their usual Western diets with Promega fish oil supplement (eicosapentaenoic acid [EPA], 0.28 g; docosahexaenoic acid [DCHA], 0.12 g; other n-3 fatty acids 0.10 g per capsule) using three protocols. Initial experiments (protocol 1 and 2) investigated the kinetics of incorporation of n-3 fatty acids into serum and neutrophil lipids after 10 capsules/d of Promega. EPA was rapidly detected in both serum and neutrophil lipids; the arachidonic acid (AA) to EPA ratio in neutrophil phospholipids showed a maximal reduction of 49:1 to 8:1 within 1 wk of beginning supplementation. EPA was preferentially incorporated into phosphatidyl-ethanolamine and phosphatidylcholine but not phosphatidylinositol. Long-term supplementation for up to 7 wk did not influence the AA/EPA ratio or the distribution of EPA among neutrophil phospholipids in a manner that was not observed after the first week. Neutrophils produced similar quantities of platelet-activating factor and slightly lower quantities of leukotriene B4 during long-term supplementation when compared with presupplementation values. Experiments examining the influence of Promega dosage indicated that the AA/EPA ratio in neutrophil lipids decreased in a dose-dependent manner. Only when the dose was increased to 15 capsules/d was there a reduction in the AA/DCHA ratio in neutrophil lipids. The quantity of AA in neutrophil lipids remained relatively constant at all supplement doses. Taken together, the current study demonstrates the capacity of n-3 fatty acids provided with a Western diet to be rapidly incorporated into neutrophil lipids. However, dietary n-3 fatty acids appear not to significantly reduce arachidonate content within neutrophil phospholipids. Constant arachidonate levels may account for the lack of large reductions in the biosynthesis of lipid mediators by neutrophils after fish-oil supplementation.